The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10495-008-0298-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polyunsaturated fatty acids as inducers of apoptosis: implications for cancer

Abstract: It has recently become clear the role played by alterations in apoptosis during the development of several chronic diseases (i.e. inflammatory, neurodegenerative and neoplastic pathologies). For this reason, the research for possible therapeutic strategies involving the modulation of the apoptotic pathways has attracted considerable interest in the past few years. In particular, it has been shown that apoptosis may be induced or inhibited by a variety of nutritional compounds providing health benefits. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 188 publications
1
101
0
2
Order By: Relevance
“…v-3 PUFAs could not only play a preventive role against CRC, but also be involved in CRC treatment, displayed as a reduction of cell growth in a time and dose-dependent manner both in vitro and in vivo with or without radiotherapy or chemotherapy [18,19]. v-3 PUFA supplementation selectively increased its concentration in the colonic mucosa and leads to a reduction in cell proliferation and an increase in apoptosis in the crypts in patients with a history of CRC [20].…”
Section: Role Of Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…v-3 PUFAs could not only play a preventive role against CRC, but also be involved in CRC treatment, displayed as a reduction of cell growth in a time and dose-dependent manner both in vitro and in vivo with or without radiotherapy or chemotherapy [18,19]. v-3 PUFA supplementation selectively increased its concentration in the colonic mucosa and leads to a reduction in cell proliferation and an increase in apoptosis in the crypts in patients with a history of CRC [20].…”
Section: Role Of Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…(61) The n-3 PUFAs might alter the growth of tumor cells by influencing cell replication, by interfering with components of the cell cycle or by increasing cell death either by way of necrosis or apoptosis. (62)(63)(64) Moreover n-3 PUFAs down-regulate the expression of Her2/neu, a well characterized oncogene that plays a key role in etiology, progression and chemo sensitivity of various types of human cancer in which this oncogene is over-expressed. Her2/neu encodes transmembrane tyrosine kinase orphan receptor p185 Her2/neu, which regulates biological functions including cellular proliferation, differentiation, motility and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these epidemiological observations, laboratory studies have shown that omega-3 PUFAs suppress the formation and growth of colorectal cancer in both established cell lines and animal models. One of the suggested underlying anticancer mechanisms is the induction of apoptosis by PUFA (9). The extensively characterized docosahexaenoic acid (DHA) is more potent at inducing apoptosis than other omega-3 PUFAs, such as eicosapentaenoic acid (10).…”
Section: Introductionmentioning
confidence: 99%
“…DHA reduces viability and triggers apoptosis in colon cancer cells while increasing the viability of normal cells (11,12), and is additionally effective in enhancing the chemosensitivity of cancer cells when administered in combination with chemo therapeutic drugs, such as doxorubicin and irinotecan (13)(14)(15). Recent studies have further demonstrated that DHA modifies the expression of key molecules critical in apoptosis, including β-catenin, survivin and XIAP (9,16). DHA activates caspase-8 and downregulates FLIP, an endogenous inhibitor of DR-mediated apoptotic signaling, in colon cancer (16), and sensitizes colon cancer cells to Fas-mediated apoptosis (17).…”
Section: Introductionmentioning
confidence: 99%